2021
DOI: 10.3390/nu13041117
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Changes and Body Mass Index during COVID-19 Pandemic Lockdown: An Italian Online-Survey

Abstract: Background. COVID-19 pandemic has imposed a period of contingency measures, including total or partial lockdowns all over the world leading to several changes in lifestyle/eating behaviours. This retrospective cohort study aimed at investigating Italian adult population lifestyle changes during COVID-19 pandemic “Phase 1” lockdown (8 March–4 May 2020) and discriminate between positive and negative changes and BMI (body mass index) variations (ΔBMI). Methods. A multiple-choice web-form survey was used to collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 10 publications
11
55
1
Order By: Relevance
“…The current systematic review, which included twenty-three studies, provides a comprehensive overview of eating behaviour characteristics associated with the COVID-19 pandemic. Consistent with previous reviews, several outcomes, such as overeating [26,31,46,47] and the influence of personal preferences on food choices [32][33][34][35]44], have been observed. However, this systematic review also found that the frequency of meals is not associated with the amount of food eaten [32,36,40].…”
Section: Discussionsupporting
confidence: 87%
“…The current systematic review, which included twenty-three studies, provides a comprehensive overview of eating behaviour characteristics associated with the COVID-19 pandemic. Consistent with previous reviews, several outcomes, such as overeating [26,31,46,47] and the influence of personal preferences on food choices [32][33][34][35]44], have been observed. However, this systematic review also found that the frequency of meals is not associated with the amount of food eaten [32,36,40].…”
Section: Discussionsupporting
confidence: 87%
“…Similar relationships are also indicated by other authors, including an increase in consumption of animal products and snacks [53,113], increasing salty snacks [32], increasing fat consumption [31], increasing 'junk food' consumption [61], snacking between meals [59], increased use of alcohol [65], and increasing sweets [34,65], especially during the lockdown. Authors [35,69,114] indicated that the stress associated with pandemic influenced on increases in emotional food of consumption, tasty but with high energy value.…”
Section: Discussionsupporting
confidence: 84%
“…The transition period associated with a pandemic situation, therefore, has the potential to change eating habits, forcing most people to stay at home, sometimes in home-offices, for long periods, often with unlimited access to food in home and less physical activity [ 28 ]. Staying at home for a long time may favor snacking between meals, eating ‘junk food’ snacks, and drinking alcohol, and it may affect the consumer’s individual choices about cooking at home, buying ready-to-eat products, as well as using takeaway food services [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The perceived risk of COVID-19 and guidelines for minimizing personal contact might have been discouraging consumers from using gastronomy during the pandemic [ 37 , 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Tárraga López et al explored the usual dietary pattern prior to confinement and assessed the adherence to the Mediterranean diet in 490 Spanish adults without evidence of clinically relevant changes in body composition [41]. A recent Italian online survey by Maffoni et al demonstrated a slight but significant increase in BMI during the COVID-19 pandemic and stratification by lifestyle changes revealed a significant variation in BMI: negative lifestyle changes were correlated with increased BMI and positive lifestyle changes with decreased BMI [42]. It is reasonable to assume that the positive impact of our dietary intervention could depend on the significant adherence rate found after only 15 days, reaching 80% after 1 month of diet.…”
Section: Discussionmentioning
confidence: 99%